Oxidative Stress Biomarkers and Lifestyles in Japanese Healthy People - Sakano, Noriko (the Society for Free Radical Research Japan, 2009)
The urinary concentrations of 8-isoprostane and 8-hydroxy-2’-deoxyguanosine (8-OHdG), which are biomarkers of oxidative stress, were measured in 677 Japanese people without any diseases, and their correlations with lifestyle facotrs, lifestyle-related blood biochemical parameters, and dietary intake of antioxidative vitamins were investigated. The mean urinary concentration of 8-isoprostane and 8-OHdG was 0.58 ng/mg creatinine and 8.43 ng/mg creatinine, respectively. Mean urinary 8-isoprostane was significantly different in terms of age, gender, smoking and alcohol consumption but not different in terms of body mass index (BMI) and exercise. By multiple regression analysis, urinary 8-isoprostane was significantly influenced by smoking and age. On the other hand, mean urinary 8-OHdG showed differences only by age group. Multiple regression analysis revealed that urinary 8-OHdG was significantly influenced by age, smoking, body weight, levels of high-sensitivity C-reactive protein (Hs-CRP) and low density lipoprotein-cholesterol in females, although it was significantly influenced by body weight in males. The present study shows that urinary 8-isoprostane is associated with lipid peroxidation related-lifestyles such as smoking, and urinary 8-OHdG is associated with arteriosclerosis related-factors such as Hs-CRP. Our findings suggest that 8-isoprostane and 8-OHdG appear to be prospective biomarkers for early prediction of lifestyle related-disease risk at the population level.